The Role of Two-Way Communication in Institutional Resilience During the COVID-19 Crisis: A Global Perspective - Hutagalung, Maasyithah; Sutrisno, Tri (Indonesian Scientific Publication, 2025)
Crisis communication has become an essential function of public institutions, particularly in light of recent global disruptions such as the COVID-19 pandemic. This narrative review investigates effective communication strategies and recurrent failures in public crisis response, aiming to uncover key factors that enhance or hinder institutional trust. A structured literature review was conducted across Scopus, Web of Science, PubMed, and Google Scholar, using targeted keywords such as